Application of Micro-Raman Spectroscopy for the Quantitative Analysis of Vitrinite Reflectance in Medium and High Rank Colombian Coals - Urbano-Noguera, Ruben Dario; Estupiñan-Duran, Hugo Armando; Neira-Arenas, Gustavo (Universidad Pedagógica y Tecnológica de Colombia, 2020)
The structural changes and the degree of maturity of three Colombian coals from the Santander and Antioquia provinces were studied using a simple and fast curve fitting method of the RBS parameters (the distance between band G and band D), FWHM - G (total width at half the maximum of the G band) and AR (area of the Raman spectrum), obtained by deconvolution and band resolution of the Micro-Raman spectra. The results were compared by morphological and chemical analysis using a SEM scanning electron microscope coupled with a solid state X - ray EDS detector. A percentage of vitrinite reflectance (% Ro) of 4.3 %, 3.8 % and 0.07 % was obtained, a percentage of carbon by EDS analysis of 91.47 %, 87.78 %, 73.4 %, a morphological description by SEM analysis presenting smooth, rough surfaces and rough-lumpy and pore size between 0.7 µm - 0.8 µm, 1.3 µm - 1.5 µm and 0.2 µm - 0.7 µm for the anthracite, semi-anthracite and bituminous samples, respectively. The results showed that based on this method, it was possible to obtain a model that allows to rapidly analyze and characterize the coal. The results compare very well to those of Colombian coals normalized by other methods to improve the precision of the measurement. The modified method, however, did not offer an appropriate fit for the lower range coal and produced extremely low reflectance values. This effect is possibly related with the molecular structure of organic matter in coal or the presence of fluorescence interference.